Minutes of 80th meeting of BRAC University campus development committee - BRAC University (Brac University, 2023)
The 80th meeting of BRAC University Campus Development Committee (CDC) was held on January 02, 2017 with A.S.M Rashidul Hai, Project Director of new campus of BRAC University in the chair. The chair welcomed all participants and commenced the business of the meeting.